AN ANALYSIS OF GRAMMATICAL ERRORS OF USING GOOGLE TRANSLATEFROM INDONESIA TO ENGLISH IN WRITING NARRATIVE TEXT - Azura Srikandi; Sholihatul Hamidah Daulay (Universitas Negeri Islam Sumatera Utara, 2022)
This study focuses on the grammatical errors made by GoogleTranslate in translating narrative text from Indonesian to English.Thenarrative text is a text written by class X culinary arts studentsat SMKTunas Karya Batang Kuis. The research method used in conductingthis research is qualitative with content analysis as the researchdesign. It is also known as the document analysis method.It is intendedthat readers will be able to learn about the types of grammar errorsthat occur when using Google Translate and also the most commonerrors. This research discovered that there are two addition errors infive narrative texts. The words are